Fresno County Young Lawyers Association Halloween Dance at Crossland's Barn - Watkins, Howard::::::::: (1984)
Polly Getz in blue denim suit, man in white jumpsuit, women in peasant outfit, Vicki Savaria wearing pink princess outfit